Phenomenology of psychiatric emergencies - Goretti, Stefano; Esposito, Cecilia Maria; Di Petta, Gilberto (Frontiers in Psychology, 2023)
Introduction Psychiatric urgency is defined as a situation of serious mental suffering and behavioral alteration, which promptly requires adequate treatment; we talk about emergency when the condition can be life-threating. Even if until now neglected by phenomenological psychopathology, the emergency issue faces a clinical management challenge in which the phenomenological method becomes fundamental. The purpose of this manuscript is then to explore the phenomenological perspective of psychiatric emergencies. The manuscript is organized into four sections: the first deals with the encounter in clinical phenomenology, the second with the life-word of the crisis, the third with the atmosphere of emergency; finally, a final section on the importance of the phenomenological method for the clinician. The encounter in clinical phenomenology The centrality of the encounter in clinical phenomenology cannot be stressed enough. It is not just the encounter between doctor and patient, but also and above all the encounter between two men, between two subjects. And it is in the affective space between them, in the intersubjectivity and intercorporeality of their encounter, that the transformative power of understanding emerges and reverberates from both sides. The approach to the other must be respectful, along the lines of the ethics of approximation, it must recognize the other as other and not overwrite it with one’s own prejudices. Otherwise, if clinicians are not sufficiently trained in the encounter, the risk is to get stuck in the anguish of the instant, to be absorbed by it, to become its tools. It is precisely the atmosphere of the emergency room that is full of expectations, haste, anxiety, which actually hinders the possibility of encountering. Instead, this possibility must be recovered, because the encounter is the founding aspect of every clinical interview, of every diagnostic suspicion, of every therapeutic resolution. The life-word of the crisis Seizing the encounter in its immediacy and in its totality, through the atmosphere that characterizes it, means for the clinician to position himself not outside the crisis, in an observational position in front of the patient, but to position himself next to him, to immerse himself in his life-world. Only then will the explosiveness of his symptoms appear to us not only as a symptomatic cascade to be contained and extinguished, but as the expression of a life-world in crisis. To use Ey’s terminology, the madness of an instant must be placed within the madness of a lifetime. The patho-gnostic structures of the psychiatrist must tune into the structures of the life-world of the crisis, with the perspective of giving meaning, of helping the subject to re-inscribe the crisis within his history, and to overcome it. The atmosphere of emergency The experience of emergency is in fact detached from daily life of our being-in-the-world, both from the clinician’s side and from that of the patient, who loses himself in this pathically charged and tense atmosphere and needs someone to walk alongside him to find the reins of his world. The context of the emergency room puts the clinician in the position of applying Strauss’s sympathetic perception of the world, made up of atmospheres, sensations, profiles, and not of eidetic knowledge. The concept of atmosphere, inaugurated by Tellenbach and taken up in recent years by several authors, appears fundamental in understanding the amalgam of emotional tension, haste and immersiveness that characterizes the emergency room environment. An atmosphere that can become oppressive, if not thematized, and that can lead the clinician to defend himself in the haste and superficiality of the intervention. The phenomenological method Psychiatric crisis is always a situation in which we are thrown, perhaps to the highest degree, and the unfolding of references between the self and the world and between the self and the others becomes an essential skill. Even in the absence of an adequate setting, in the intersection between several pressures, the phenomenological method retains its panoramic gaze intact. We define it panoramic because it does not aim only at the observation and description of the present phenomena, which are generally characterized by violence, anguish, chaos. It is through the suspension of the epochè that the clinician can distance himself from the oppressive atmosphere of the crisis and grasp the coordinates of the patient’s life-world. Only with this attitude does an authentic encounter become possible even in the difficult situation of emergency, paving the way for the challenge of care.